Effect of regrowth age and climatic factors on primary metabolites content of Tithonia diversifolia - Ramírez-Pérez, Y.; Herrera-Herrera, Rocío C.; Verdecia, D. M.; Herrera, R. S.; Chacón-Marcheco, E.; Ledea, J. L.; Ramírez, J. L. (Cuban Journal of Agricultural Science, 2023)
Primary metabolites, very abundant in nature, are essentials for the physiological development of the plant; which are in great amount and of easy extraction. With the objective of evaluating the effect of the plant maturity and the climatic factors on the primary metabolites content in Tithonia diversifolia theexperiment was developed, according to a random block design, with three treatments (60, 120 and 180 days) and four replications. Contents of nitrogen, glucose, fructose and sucrose were evaluated through analysis of variance, correlation and regression with the SPSS statistical system, version 22.0 The contents of nitrogen, glucose, sucrose and fructose during the two seasonal periods in T. diversifolia decreased with the regrowth age (from 60 up to 180 days) in 13.15, 0.008, 0.015 and 0.007 g.kg-1 for the rainy period, while for the dry season were 17.39, 0.002, 0.003 and 0.0009 g.kg-1, respectively. Quadratic regression equations were fitted with the regrowth age for all the indicators. All regression coefficients were higher to 0.95 for primary metabolites in both seasonal periods, except for sucrose and fructose during the dry season was 0.93 and 0.9, respectively.The correlations were very changeable were the rainy days were related with all primary metabolites during the rainy season, while during the dry season only nitrogen showed significant correlation. The functions explained the close correspondence between growth and the primary metabolites content and the fluctuations found in the sugars influenced by the shrub phenological state and their photosynthetic activity. Key words: shrub, equations, age, climate, metabolites, Tithonia